On the Question of New Forms of Urbanization in the Context of Spatial Development Management in the Republic of Karelia. Article Two - S. L. Katanandov; V. V. Solodilov; V. A. Shamakhov (Управленческое консультирование)
In modern conditions, classical approaches to urbanization need to be supplemented. The concept of rural agglomerations based on the development of inter-territorial cooperation of local governments arose. The question about new criteria for the formation of agglomerations was raised. The concept of actual urban settlements, which involves taking into account the modern characteristics of environmental processes is proposed. The territorial base is the southern part of the Republic of Karelia.